Reexploration of the peritoneal cavity in the bed: Modified Beveraggi technique - Bogliaccini, Gustavo; Pomi, Jorge; Estefan, Alberto; Praderi, Alberto; Praderi, Alberto (Cirugía del Uruguay, 1982)
A modification of Beveraggi 's procedure of abdominal closure with Marlex mesh in septic patients of abdominal origin is presented. The type of fixation of the mesh allows abdominal exploration in the ward. Sorne considerations over the foundations and indications of the procedure are done and our cases are presented.